Vibration Impact Acoustic Emission Technique For Identification And Analysis Of Defects In Carbon Steel Tubes: Part A Statistical Analysis - Abd Halim, Zakiah; Jamaludin, Nordin; Junaidi, Syarif; Syed Yahya, Syed Yusainee (2015)
Current steel tubes inspection techniques are invasive, and the interpretation and evaluation of inspection results are manually done by skilled personnel. This paper presents a statistical analysis of high frequency stress wave signals captured from a newly developed noninvasive,non-destructive tube inspection technique known as the vibration impact acoustic emission (VIAE) technique. Acoustic emission(AE) signals have been introduced into the ASTM A179 seamless steel tubes using an impact hammer, and the AE wave propagation was captured using an AE sensor. Specifically, a healthy steel tube as the reference tube and four steel tubes with through-hole artificial defect at different locations were used in this study. The AE features extracted from the captured signals are rise time, peak amplitude,duration and count. The VIAE technique also analysed the AE signals using statistical features such as root mean square (r.m.s.), energy,and crest factor. It was evident that duration, count, r.m.s., energy and crest factor could be used to automatically identify the presence ofdefect in carbon steel tubes using AE signals captured using the non-invasive VIAE technique.